Empowering Coastal Communities: Training on Making Floating Nets - Mahmud Mustain; Wahyudi Wahyudi; Haryo Dwi Armono; Muhammad Zikro; Yeyes Mulyadi (LPPM UNINUS, 2021)
Based on the results of the study program conducted by the Kangean Island Coastal Community with the theme: